Behuria lumiarensis (Melastomataceae), a new species on a mountaintop of the Brazilian Atlantic Forest - Bochorny, Thuane; Michelangeli, Fabian A.; Goldenberg, Renato (Phytotaxa, 2017)
We describe and illustrate Behuria lumiarensis, a new species from the state of Rio de Janeiro, Brazil. It has been collected only once in montane vegetation in the Municipality of Nova Friburgo. The new species can be recognized by the combination of leaf blades with adaxial surface covered with sessile glands and abaxial surface moderately covered with stalked glands only on the veins, hypanthium sparsely covered with stalked glands, a large calyx tube with narrow sepals that are not apiculate in the apex, small petals, and glabrous ovary apex.